48.4: General Metrology Framework for Determining the Ambient Optical Performance of Flat Panel Displays. Issue 1 (June 2015) - Penczek, John; Kelley, Edward F.; Boynton, Paul A.
Abstract : A framework is described which allows a generalized treatment of display ambient characteristics. The proposed methodology incorporates both display reflection and transmission properties. An LCD and OLED transparent display are used as an example to demonstrate the utility of this framework.